Pengaruh Financial Literacy, Income, Hedonism Lifestyle, Self-Control, dan Risk Tolerance terhadap Financial Management Behavior pada Generasi Milenial Kota Surabaya - Alfrin Erman Sampoerno; Nadia Asandimitra Haryono (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
Financial management behavior is organized, regulated, managed, and saved funds to achieve financial well-being. The study aims to effects of financial literacy, income, hedonistic lifestyle, self-control, and risk tolerance on financial management behavior. The object used in this research is the millennial generation based in Surabaya with a monthly income. This study focuses on the millennial generation since they are stigmatized for their excessive consumption and inability to conserve money. This study employs quantitative research and the Structural Equation Model as a method of analysis (SEM). A total of 200 people responded to the survey. According to this study, financial management behavior is influenced by hedonistic lifestyle and self-control, but not by financial literacy, income, or risk tolerance. This finding is because most respondents are still in college, and the study's limitations include the inability to include other variables such as intention and social standing. This study could be helpful to reference for various parties, especially the millennial generation, to be better at self-controlling their consumption and increase their financial literacy.